2018
DOI: 10.1002/cbic.201800077
|View full text |Cite
|
Sign up to set email alerts
|

siRNA Modified with 2′‐Deoxy‐2′‐C‐methylpyrimidine Nucleosides

Abstract: (2'S)-2'-Deoxy-2'-C-methyluridine and (2'R)-2'-deoxy-2'-C-methyluridine were incorporated in the 3'-overhang region of the sense and antisense strands and in positions 2 and 5 of the seed region of siRNA duplexes directed against Renilla luciferase, whereas (2'S)-2'-deoxy-2'-C-methylcytidine was incorporated in the 6-position of the seed region of the same constructions. A dual luciferase reporter assay in transfected HeLa cells was used as a model system to measure the IC values of 24 different modified duple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…4 ) were evaluated for their influence on strand specific activity. 90 These modifications were tested at positions AS:5, AS:6 AS:20 and SS:20. Modification of position AS:20 with either R or S configuration was found to improve the IC 50 .…”
Section: Internal Modificationsmentioning
confidence: 99%
“…4 ) were evaluated for their influence on strand specific activity. 90 These modifications were tested at positions AS:5, AS:6 AS:20 and SS:20. Modification of position AS:20 with either R or S configuration was found to improve the IC 50 .…”
Section: Internal Modificationsmentioning
confidence: 99%
“…[76] Another conformationally restricted nucleotides investigated by our group were 2'-deoxy-2'-C-methylpyrimidine nucleosides (Figure 3). [77] Specifically, (2'S)-2'-Deoxy-2'-Cmethyluridine, (2'R)-2'-deoxy-2'-C-methyluridine and (2'S)-2'-deoxy-2'-C-methylcytidine were incorporated in the 3'overhang regions of the sense and antisense strands and in the seed region of siRNA duplexes. The best results were obtained by the substitution of one thymidine unit in the antisense 3'overhang region by (2'S)-or (2'R)-2'-deoxy-2'-C-methyluridine, increasing the inhibitory potency twice of the value observed for the unmodified siRNA control.…”
Section: Modified Sirna Carrying Non-natural Nucleosidesmentioning
confidence: 99%
“…Another parameter that was studied was the possibility of incorrect strand selection by RISC using specific plasmids that can measure the silencing activity of the guide or the passenger strand. It was found that the presence of 2’‐deoxy‐2’‐ C ‐methylpyrimidine nucleosides can increase the selectivity of the modified siRNA, especially when these modifications were located in positions 5 and 6 of the seed region [77] …”
Section: Chemical Modification In Sirnamentioning
confidence: 99%
See 1 more Smart Citation